Sintesis dan Karakterisasi Bunga Sepatu dan Karbon Kayu Ulin Untuk Katalis Pada Proses Pirolisis Sampah Plastik - Guruh Sartika; Yano Hurung Anoi; Rosmiati; Asriwulan; Tatang Wiyadi; Amir Maulana; Ahmad Yani (TURBO [Tulisan Riset Berbasis Online], 2026)
Plastic waste pyrolysis requires catalysts that are thermally stable, accessible, and economically viable. This study synthesizes and characterizes a biomass-based catalytic material derived from hibiscus flower powder and activated Ulin wood carbon. Hibiscus petals were dried under sunlight for 6 h, oven-dried at 55 °C for 1 h, ground, and sieved to 200 mesh. Ulin wood carbon was reduced by high-energy milling, sieved to 200 mesh, activated in 3 M NaOH using 8 g carbon for 12 h, washed to pH 6–7, and dried at 105 °C for 8 h. UV–Vis analysis showed that hibiscus powder contained 676.62 mg EQ/100 g flavonoids, 2305.06 mg GAE/100 g phenols, 369.69 ppm antioxidant activity, and 122.40 ppm anthocyanins. Activated Ulin carbon contained 166.28 mg EQ/100 g flavonoids, 32.04 mg GAE/100 g phenols, 0 ppm antioxidant activity, and 0.54 ppm anthocyanins. Thermal, morphological, functional group, and crystallinity analyses were conducted using TGA-DTA, SEM, FTIR, and XRD. The results indicate that hibiscus contributes oxygenated bioactive compounds, whereas activated Ulin carbon provides a carbonaceous support structure. The combined characteristics suggest potential use as a sustainable catalyst precursor for plastic waste pyrolysis. Keywords: Hibiscus flower; ulin wood carbon; activated carbon; biomass catalyst; plastic waste pyrolysis